2023
DOI: 10.3390/nu15184049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Doses of Caffeine Supplementation on Collegiate Male Volleyball Players’ Specific Performance and Skills: A Randomized, Double-Blind, Placebo-Controlled, Crossover Study

Javad Nemati,
Mohammad Hemmatinafar,
Alireza Niknam
et al.

Abstract: Background: The improvement of performance and skill indices of volleyball players can affect their success rate. Therefore, the present study aimed to evaluate the effects of acute caffeine supplementation of varied doses on collegiate volleyball players’ specific performance and skills. Method: This research was a randomized, double-blind, crossover design study in which 15 male volleyball players aged 18 to 25 years participated voluntarily. Participants were randomly placed in three different conditions, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 62 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…A randomized, double-blind crossover study of upper body muscle strength in female habitual caffeine users showed that an acute ingestion of 6 mg/kg BW of caffeine resulted in a significant boost in barbell speed during the bench press, as compared to the ingestion of 3 mg/kg BW [ 59 ]. In addition, Nemati et al [ 60 ] showed that 6 mg/kg BW of caffeine was more effective in enhancing lower body muscle strength in collegiate male volleyball players compared to 3 mg/kg BW. This may be due to the fact that caffeine at ≥6 mg/kg BW better promotes Ca 2+ release and enhances the contractility of skeletal muscle, making the potentiating effect significant.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized, double-blind crossover study of upper body muscle strength in female habitual caffeine users showed that an acute ingestion of 6 mg/kg BW of caffeine resulted in a significant boost in barbell speed during the bench press, as compared to the ingestion of 3 mg/kg BW [ 59 ]. In addition, Nemati et al [ 60 ] showed that 6 mg/kg BW of caffeine was more effective in enhancing lower body muscle strength in collegiate male volleyball players compared to 3 mg/kg BW. This may be due to the fact that caffeine at ≥6 mg/kg BW better promotes Ca 2+ release and enhances the contractility of skeletal muscle, making the potentiating effect significant.…”
Section: Discussionmentioning
confidence: 99%
“…Using block randomization, eligible participants were randomly assigned in a 1:1 ratio to either the supplement or placebo group [ 27 ]. Participants were instructed to avoid consuming caffeinated sources and perform vigorous exercise ≥24 h before the experiment to control for any acute and side effects on the measured variables [ 28 ]. The randomization allocation table was created by a study team member blinded to assessments; allocation numbers were then placed in sealed envelopes ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Of the used supplements by athletes, caffeine stands as an effective supplement for neuromuscular, metabolic, and cardiovascular functions, leading to enhanced technical and physical performance. Caffeine is particularly renowned for its acute and chronic impact on athletic performance 20 . Caffeine is a potent supplement that can boost energy expenditure after physical activity 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is particularly renowned for its acute and chronic impact on athletic performance 20 . Caffeine is a potent supplement that can boost energy expenditure after physical activity 20 . It is a widely consumed bioactive substance in our diet and is known to stimulate the central nervous system 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation